“Wise Passiveness”: Wordsworth, Spinoza, and the Ethics of Passivity - LeClerc, Jérémie (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2021)
This article frames the poetry of William Wordsworth and the philosophical writings of Spinoza as mutually illuminating works exploring the ethical and ontological questions raised by bodies in states of passivity and immobility. Both writers, it argues, revise our idea of what a “powerful” body might be by developing the concept of “dynamic passivity”—a passivity that does not stand in simple opposition to states of activity, and that ought to be cultivated rather than overcome in the process of empowering the body. The article examines and contrasts the different ways in which Wordsworth and Spinoza conceive of this dynamic passivity, with particular attention paid to how the former embeds a cultivation of “wise passiveness” for the reader in the very form of his poems, through a variety of elements like syntax, metre, and acoustic effects.